A prospective cohort study of the silk fibroin patch in chronic tympanic membrane perforation. (13th June 2016) - Lee, Jun Ho; Kim, Dong‐Kyu; Park, Hae Sang; Jeong, Ju Yeon; Yeon, Yeung Kyu; Kumar, Vijay; Bae, Sung Hee; Lee, Jung Min; Moon, Bo Mi; Park, Chan Hum
Abstract : Objectives/Hypothesis: Silk fibroin patching has been used to repair acute tympanic membrane perforations. Here, we describe the advantages and outcomes of this technique for chronic tympanic membrane perforations. Study Design: Individual cohort study. Methods: Forty patients were enrolled; half underwent perichondrium myringoplasty, and the silk fibroin patch technique was applied in the remaining patients. We compared the closure, otorrhea, and complication rates; closure time; postoperative hearing gain; and patient satisfaction between the two groups. Results: Demographic data (gender, site, age, duration, preoperative air‐bone gap, and perforation size and location) were not significantly different between the two groups. The closure rates and times, complication rates, and postoperative hearing gains were also similar in both groups. The mean operative time, otorrhea rate, and complication rate were also significantly better in the silk fibroin patch group. The intraoperative dizziness scores were higher in the conventional perichondrium myringoplasty group. Conclusions: Success rates were similar for the silk fibroin patch technique and conventional perichondrium myringoplasty; however, patching was an easier, faster procedure. Our results suggest that the silk fibroin patch technique is a suitable treatment for chronic tympanic membrane perforation. Level of Evidence: 2b Laryngoscope, 126:2798–2803, 2016